1998
DOI: 10.1002/(sici)1098-108x(199809)24:2<217::aid-eat11>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Lipid levels in anorexia nervosa

Abstract: Objective Anorexia nervosa is a chronic disorder characterized by the patient's refusal to maintain body weight and a myriad of medical complications. Two frequently cited and poorly understood complications are hypercholesterolemia and hypercarotenemia. We therefore measured fasting cholesterol and beta‐carotene levels in a cohort of moderately severe anorectics. Method: All subjects were female and met DSM‐IV criteria for anorexia nervosa. Lipid profiles and beta‐carotene levels were determined in 23 female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
20
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 10 publications
6
20
0
1
Order By: Relevance
“…The higher concentrations were based on higher LDL-Chol levels, as also described in previous studies (Mordasini et al 1978), but not confirmed by others (Arden et al 1990;Mehler et al 1998). The mean difference between CO and AN in our present study was rather small, in contrast to markedly elevated Chol levels found in reasonably large cohorts in early reports in the literature (Klinefelter, 1965; Crisp et al 1968;Mehler et al 1998;Mordasini et al 1978). A high degree of selection of patients of certain subgroups in these studies could be the reason.…”
Section: Discussionsupporting
confidence: 63%
“…The higher concentrations were based on higher LDL-Chol levels, as also described in previous studies (Mordasini et al 1978), but not confirmed by others (Arden et al 1990;Mehler et al 1998). The mean difference between CO and AN in our present study was rather small, in contrast to markedly elevated Chol levels found in reasonably large cohorts in early reports in the literature (Klinefelter, 1965; Crisp et al 1968;Mehler et al 1998;Mordasini et al 1978). A high degree of selection of patients of certain subgroups in these studies could be the reason.…”
Section: Discussionsupporting
confidence: 63%
“…features [19,20]. The level was normalized by rhGH, indicating that this AN-specific metabolism of HDLcholesterol is partly related to the insufficient action of GH in this syndrome.…”
Section: Discussionmentioning
confidence: 87%
“…It is well documented that hypercholesterolemia is present in patients with AN [19,20]. Administration of rhGH decreased total cholesterol level.…”
Section: Discussionmentioning
confidence: 98%
“…However, the serum total cholesterol values in patients with AN in previously published papers were widely distributed (10,11,(17)(18)(19)(20)(21). Although the frequency of cardiac events in patients with BN is not clear, the serum cholesterol values in patients with BN were also widely distributed (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 93%
“…The implications of the long-term elevation of cholesterol influencing the morbidity in eating disorders must not be neglected. Given the chronicity of this condition, the development of elevated concentrations of cholesterol at an early age may increase the risk of atheroma formation and ischemic heart disease (20,31).…”
Section: Discussionmentioning
confidence: 99%